Adequate Surgical Planning for Epidural Hematoma from Sinus Transversus Bleeding: A Case Report - Oley, Maximillian Ch.; Prasetyo, Eko; Tjungkagi, Ferdinand; Manuhutu, Yovanka N.; Tora, Doddy (Medical Scope Journal, 2025)
Abstract: Epidural hematomas can be caused by bleeding into the dural sinuses. In an epidural hematoma case, suspected sinus transversus involvement requires a specific examination with therapeutic management involving early diagnosis, planning, and adequate surgical technique. We reported a 21-year-old woman admission with a main complaint of decreased consciousness for two hours with Glasgow Coma Scale (GCS) score 12. CT-Scan revealed an epidural hematoma in the right temporoparietooccipital region and midline shift of 5.24 mm to the left with linear fracture of the right temporal bone. Craniotomy was performed, and intraoperatively there was a distasis fracture of lambdoidea sutura, but after bone was elevated and hemmorhage was evacuated, there was still bleeding from the right sinus transversus; therefore, duramater was hang off, packed the sinus with patties and surgicell, and there was no bleeding anymore. This was a rare and difficult case due to the fracture in the lambdoidea area. The main post-operative complication was sinus thrombosis, especially after post-repair stenosis or extrinsic compression of the sinus. The patient’s outcome was a better GCS than of the first admission. In conclusion, the present case and discussion highlight the many details and technical specificities to be taken into account by neurosurgeons when encountering epidural hematoma caused by sinus transversus, which are pivotal in determining the efficacy of the approach and prognosis of the patient. Keywords: epidural hematoma; sinus transversus; Glasgow coma scale